The neglected season: Warmer autumns counteract harsher winters and promote population growth in Arctic reindeer. (15th December 2020) - Loe, Leif Egil; Liston, Glen E.; Pigeon, Gabriel; Barker, Kristin; Horvitz, Nir; Stien, Audun; Forchhammer, Mads; Getz, Wayne Marcus; Irvine, Robert Justin; Lee, Aline; Movik, Lars K.; Mysterud, Atle; et al.
Abstract: Arctic ungulates are experiencing the most rapid climate warming on Earth. While concerns have been raised that more frequent icing events may cause die‐offs, and earlier springs may generate a trophic mismatch in phenology, the effects of warming autumns have been largely neglected. We used 25 years of individual‐based data from a growing population of wild Svalbard reindeer, to test how warmer autumns enhance population growth. Delayed plant senescence had no effect, but a six‐week delay in snow‐onset (the observed data range) was estimated to increase late winter body mass by 10%. Because average late winter body mass explains 90% of the variation in population growth rates, such a delay in winter‐onset would enable a population growth of r = 0.20, sufficient to counteract all but the most extreme icing events. This study provides novel mechanistic insights into the consequences of climate change for Arctic herbivores, highlighting the positive impact of warming autumns on population viability, offsetting the impacts of harsher winters. Thus, the future for Arctic herbivores facing climate change may be brighter than the prevailing view. Abstract : It is a prevailing view in science and media that Arctic herbivores are doomed because winters get wetter and icier and blocks access to pastures. Combining life‐history data of 839 known‐aged Svalbard reindeer followed over 25 years, with GPS‐tracking data and snow modelling, we demonstrate that snow‐onset, in autumn, was equally important for late winter body mass and population dynamics as icy winters, which previously have received most attention. This suggests that the positive effect of warm autumns shortening winters compensates for the fact that they are also harsher.